Is cryoballoon ablation preferable to radiofrequency ablation for treatment of atrial fibrillation by pulmonary vein isolation? A meta-analysis. - Junxia Xu; Yingqun Huang; Hongbin Cai; Yue Qi; Nan Jia; Weifeng Shen; Jinxiu Lin; Feng Peng; Wenquan Niu (PLoS ONE)
Objective Currently radiofrequency and cryoballoon ablations are the two standard ablation systems used for catheter ablation of atrial fibrillation; however, there is no universal consensus on which ablation is the optimal choice. We therefore sought to undertake a meta-analysis with special emphases on comparing the efficacy and safety between cryoballoon and radiofrequency ablations by synthesizing published clinical trials. Methods and results Articles were identified by searching the MEDLINE and EMBASE databases before September 2013, by reviewing the bibliographies of eligible reports, and by consulting with experts in this field. Data were extracted independently and in duplicate. There were respectively 469 and 635 patients referred for cryoballoon and radiofrequency ablations from 14 qualified clinical trials. Overall analyses indicated that cryoballoon ablation significantly reduced fluoroscopic time and total procedure time by a weighted mean of 14.13 (95% confidence interval [95% CI]: 2.82 to 25.45; P = 0.014) minutes and 29.65 (95% CI: 8.54 to 50.77; P = 0.006) minutes compared with radiofrequency ablation, respectively, whereas ablation time in cryoballoon ablation was nonsignificantly elongated by a weighted mean of 11.66 (95% CI: -10.71 to 34.04; P = 0.307) minutes. Patients referred for cryoballoon ablation had a high yet nonsignificant success rate of catheter ablation compared with cryoballoon ablation (odds ratio; 95% CI; P: 1.34; 0.53 to 3.36; 0.538), and cryoballoon ablation was also found to be associated with the relatively low risk of having recurrent atrial fibrillation (0.75; 0.3 to 1.88; 0.538) and major complications (0.46; 0.11 to 1.83; 0.269). There was strong evidence of heterogeneity and low probability of publication bias. Conclusion Our findings demonstrate greater improvement in fluoroscopic time and total procedure duration for atrial fibrillation patients referred for cryoballoon ablation than those for radiofrequency ablation.